Spain: socio-economic development in the context of the present demographic challenge - Galina N. Ponedelko (Научно-аналитический вестник Института Европы РАН)
The article considers the problems of today’s demographic crisis in Spain and its negative consequences for the future sustainable socio-economic development of the country. Predicted for 2050 the shifts in the age structure of the population and a reduction in it the share of the most working-age group (from 16 to 45 years) with a simultaneous sharp increase (up to 30%) in the oldest age group of the population (over 65 years) will lead to further depopulation of a significant part of the country’s territory, a reduction in the number and the share of the employed population, an increase in the burden on the pension and health care systems and a weakening of the potential of the welfare state. The response to these very negative consequences of the demographic challenge should be the most decisive actions of the Spanish government, the main one of which is the reform of the education system, aimed at improving of the quality of human capital and the level of professionalization of the country’s population.